Edukasi Auto Streching pada Kasus Nyeri Leher pada Siswa SMP Nurul Ilmi Kota Jambi - Wanti Hasmar; Faridah Faridah; Indah Permata Sari (Jurnal Abdimas Kesehatan (JAK), 2023)
Neck pain is a complaint that often causes a person to come to a health facility for treatment. Auto stretching is a technique of stretching the muscles with the correct direction of pulling which is done independently with the aim of reducing pain. Based on the data collected, it was found that (80%) junior high school students who had less knowledge and had sufficient knowledge 3 (15%). After conducting counseling on reducing neck pain with auto stretching, there was an increase in the knowledge of junior high school students with a percentage of 5% increasing to 90%. The aim of this counseling to the community is to increase the knowledge of junior high school students about auto stretching in cases of neck pain. Methods Implementation of counseling activities is carried out by lecture and demonstration methods with a total of 20 participants. The material presented about auto stretching in neck pain includes the meaning, causes, pathophysiology of neck pain, as well as understanding, benefits, how to implement auto stretching. In counseling, discussions were also held between the presenters and participants to share experiences related to the theme of neck pain. To find out the participants' understanding of the material presented, an evaluation was held by asking a number of questions. The results of this activity showed an increase in junior high school students' knowledge about auto stretching for neck pain